Atomic energy—Key to industrial progress - Sigvard Eklund (Intereconomics, 1969)
The International Atomic Energy Agency came into legal existence on the 29th July, 1957. It now has 101 Member States who meet annually in the General Conference. A Board of Governors consisting of 25 Member States carries out the functions of the Agency in accordance with the Statute. The IAEA is an autonomous body linked to the United Nations and a number of its Specialised Agencies by relationship agreements, but itself not a Specialised Agency. In pursuance of its first objective to promote the peaceful use of the atom for the welfare of man, the Agency is engaged in a wide spectrum of activity which could be considerably extended by the Non-proliferation Treaty. In Vienna we interviewed the Director General of the IAEA about certain aspects of the Agency's present and future work.
Keywords: 330; Interview